Co-assembly of Fmoc-tripeptide and gold nanoparticles as a facile approach to immobilize nanocatalysts. Issue 26 (9th March 2017) - Zhang, Yifei; Liu, Xiaojing; Wang, Mengfan; Zhao, Yanan; Qi, Wei; Su, Rongxin; He, Zhimin
Abstract : AuNPs are immobilized onto peptide-based nanofibers through co-assembly Fmoc-FFX and nanoparticles, which shows favorable catalytic activity toward 4-nitrophenol. Abstract : A facile approach was developed to immobilize gold nanoparticles (AuNPs) onto peptide nanofibers for catalytic applications. In this study, fluorenylmethoxycarbonyl diphenylalanine (Fmoc-FF) was conjuncted with histidine, arginine or cysteine at their C-terminus to provide binding sites for AuNPs. The co-assembly of Fmoc-tripeptide and AuNPs was achieved by dropping the peptide monomer solution directly into the AuNP solution, leading to the formation of nanofibers and the immobilization of AuNPs in one step. Atomic force microscopy, transmission electron microscope and circular dichroism analyses demonstrated that the presence of AuNPs does not significantly change the morphology and secondary structure of the nanofibers. The histidine-containing peptide-immobilized AuNPs were found to display favorable catalytic activity and stability for the reduction of 4-nitrophenol to 4-aminophenol. The present approach to fabricating nanomaterial-supported AuNPs may be extended to the production of other nanoparticle-containing composites in the fields of catalysis, sensing and biomedicine.